1978
DOI: 10.1093/oxfordjournals.aje.a112572
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Kepone Poisoning in Chemical Workers

Abstract: From March 1974 through July 1975, 76 (56%) of 133 persons who had worked at a pesticide plant that produced Kepone, a chlorinated hydrocarbon insecticide, contracted a previously unrecognized clinical illness characterized by nervousness, tremor, weight loss, opsoclonus, pleuritic and joint pain, and oligospermia. Illness incidence rates for production workers (64%) were significantly higher than for nonproduction personnel (16%). The mean blood Kepone level for workers with illness was 2.53 ppm and for those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
98
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(107 citation statements)
references
References 0 publications
5
98
1
Order By: Relevance
“…Between March 1974 and July 1975 grossly excessive and uncontrolled occupational exposure to this chlorinated hydrocarbon insecticide took place at a small chemical plant in Hopewell, Virginia. Of a total of 133 workers exposed, 57% (76 workers) developed acute neurologic illness involving tremor and nervousness (12). Similar illness had previously been observed in laboratory animals (13).…”
Section: Keponesupporting
confidence: 67%
“…Between March 1974 and July 1975 grossly excessive and uncontrolled occupational exposure to this chlorinated hydrocarbon insecticide took place at a small chemical plant in Hopewell, Virginia. Of a total of 133 workers exposed, 57% (76 workers) developed acute neurologic illness involving tremor and nervousness (12). Similar illness had previously been observed in laboratory animals (13).…”
Section: Keponesupporting
confidence: 67%
“…In humans, chlordecone exposure in occupational circumstances has been associated with a well recognized clinical syndrome involving the nervous system, liver, and testes (Cannon et al, 1978;Cohn et al, 1978;Taylor et al, 1978). Experimental studies in animals confirm all of the toxic effects observed in humans (Faroon et al, 1995).…”
Section: Introductionmentioning
confidence: 94%
“…The third pesticide known to cause alterations in semen quality is the chlorinated hydrocarbon insecticide chlordecone (Kepone). In a study conducted in 1974, Cannon et al (79) characterized an outbreak of a new disease in 57% of 133 persons working in a Keponeproducing chemical plant with virtually uncontrolled exposure to high doses of chlordecone. Semen samples revealed oligozoospermia with predominating abnormal and nonmotile spermatozoa.…”
Section: Effects Of Pesticides On Semen Qualitymentioning
confidence: 99%